Sinh thiết mô dưới hướng dẫn siêu âm - Cân, Nguyễn Đình; Quân, Nguyễn Phước Bảo; Vân, Nguyễn Thị Cẩm; Phương , Nguyễn Thị Lan; Hồng, Nguyễn Văn (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.